2020
DOI: 10.1101/2020.04.22.054742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent neuroimaging and neurostimulation reveals a causal role for dlPFC in coding of task-relevant information

Abstract: The way in which the brain prioritises processing of information relevant for our current goals is widely contested. Many studies implicate the dorsolateral prefrontal cortex (dlPFC), and propose that it drives brain-wide focus by biasing processing in favour of relevant information. An alternative, however, is that dlPFC is involved in the inhibition of irrelevant information. Here, we address this longstanding debate using the inferentially powerful approach of applying transcranial magnetic stimulation duri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…In addition, Woolgar and colleagues (2015) found stronger visual object coding in the MD cortex for cued (i.e., attended, task-relevant) objects relative to equivalent distractor objects, and Jackson and colleagues (2016) reported stronger MD coding of cued compared to equivalent distractor features of the same object. Moreover, MD coding of cued information can be selectively impaired by non-invasive stimulation the right dorsolateral prefrontal cortex, one of the nodes in the MD network (Jackson et al, 2020). In parallel, recent magnetoencephalography (MEG) studies have shown the coding of a cued feature at a cued location is sustained over time, while information coding for distractor information is not sustained (Battistoni et al, 2018; Goddard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Woolgar and colleagues (2015) found stronger visual object coding in the MD cortex for cued (i.e., attended, task-relevant) objects relative to equivalent distractor objects, and Jackson and colleagues (2016) reported stronger MD coding of cued compared to equivalent distractor features of the same object. Moreover, MD coding of cued information can be selectively impaired by non-invasive stimulation the right dorsolateral prefrontal cortex, one of the nodes in the MD network (Jackson et al, 2020). In parallel, recent magnetoencephalography (MEG) studies have shown the coding of a cued feature at a cued location is sustained over time, while information coding for distractor information is not sustained (Battistoni et al, 2018; Goddard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, both rule and relevant stimulus information can typically be decoded from MD regions in human fMRI (Jackson et al, 2016;Woolgar, Afshar, et al, 2015;Woolgar & Zopf, 2017) and from frontal cortex in non-human primate single-unit recordings (Everling et al, 2006;Stokes et al, 2013). Disrupting prefrontal function causes reduction in task-relevant information coding (Jackson et al, 2021), and incorrect rule or stimulus information coding predicts incorrect behavioural responses (Woolgar et al, 2019). Moreover, the structure of frontal stimulus information predicts subsequent occipital stimulus information as attentional selection of relevant features emerges (Goddard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MD coding for task-relevant stimuli is enhanced when stimuli are more difficult to discriminate (Woolgar, Hampshire, et al, 2011; and changes to prioritise information that is at the focus of attention (Jackson & Woolgar, 2018;. Activity in at least one MD region appears to be causal for facilitating taskrelevant information processing (Jackson et al, 2021). This, in turn, may provide a source of bias to more specialised brain regions, for example through task-dependent connectivity (Cole et al, 2013; see for example Baldauf & Desimone, 2014).…”
mentioning
confidence: 99%
“…One approach is to remove the affected slices or volumes via temporal interpolation (Fig. 1a) [6, 7, 15]. This can be controlled to result in minimal information loss [16] but is laborious and requires careful assessment to ensure that all affected slices have been removed.…”
Section: Introductionmentioning
confidence: 99%
“…However, offline approaches are not suited for all paradigms, for example, trial-by-trial investigations or where the timing of TMS delivery is critical, and are limited by the duration of the induced TMS effect. Thus, several studies have adopted concurrent methods, for example, to investigate causal influences of higher order brain areas on specialised cortices [2][3][4][5][6][7]. Recently there has been a resurgence of interest in concurrent TMS-fMRI, for example combining with modern analytical techniques for causal insights into information processing [8,9].…”
Section: Introductionmentioning
confidence: 99%